Mothers’ Perception of Growth Monitoring and Factors Influencing growth monitoring of Under-five children in Sagamu, Ogun State (2021)
Growth monitoring is a measure of nutritional status of children especially those of under-five children. The perception of mothers of under-five could affect the growth monitoring of their children, hence understanding their perceptions is very important. This study was carried out to assess mothers' perception of growth monitoring and factors influencing growth of under-five children in Sagamu, Ogun state. This cross-sectional descriptive study was conducted among mothers of under-five in Sagamu, Nigeria. A Multistage sampling method was used to select respondents for the study. A self-administered structured questionnaire was used for data collection. Data collected was analysed and presented in frequency/percent tables. Ethical clearance for the study was obtained from UVUCH Ethical Review Committee. Out of 394 respondents, 246 (62.4%) were young mothers, 221 (56.1%) of their children were female. Also, 237 (60.2%) of the children were infants, 102 (25.9%) were toddlers, while 55 (14.0%) were pre- school children. Moreover, 343 (87.1%) respondents were Christians and the remaining Moslems. Furthermore, 77.2%) of the mothers strongly agreed that the growth of their children should be monitored, and 76.6% strongly agreed that mothers should be involved in growth Mother's Perception of Growth Monitoring and Factors Influencing Growth of under... 19 monitoring of their children. Their perception about growth monitoring was generally good. In addition, 248 (62.9%) of the mothers had adequate health knowledge on growth monitoring. The higher the knowledge of factors influencing child growth among mothers the better their perception towards growth monitoring. Therefore, mothers should be equipped with relevant health information to enhance healthy perception and attitudes.